Actions of the nurse to the patient with a mental disorder (Research, Society and Development, 2021)
The psychiatric reform that took place in Brazil carries characteristics of other movements that occurred in other parts of the world. The idea common to all movements is the struggle for the rights of the individual in mental suffering, seeking mainly the rupture of the mental model. These changes led to several transformations in the care scenario, for all professions directly linked to the patient. Nursing in turn has experienced and experiences significant changes in the provision of care. The aim of this study is to talk about nursing care for patients affected by mental disorder, making a temporal analysis of how this care occurred and how it presents itself in the current mental health conjuncture. The methodology is of the literature review type, which occurred through research in the databases BIREME, Lilacs, Scielo, BDENF and VHL. For this, the descriptors: nursing care for people with disorders were selected; nursing care for patients with mental disorders. In view of the results, it was evidenced that nurses are an important part of caring for patients with mental disorders, noting that these make up a multidisciplinary team and highlighting that care goes far beyond just caring for the patient, but that it consists mainly in the relationship with the patient's family, in bonding, in the work that aims at social reintegration and often also the family reinsertion of the individual. Profession that needs to undergo constant updates, but has experienced numerous transformations throughout this period of Reformation.